My Math Forum Simple(st) Proof of Fermat's Last Theorem.

 Number Theory Number Theory Math Forum

 July 11th, 2017, 09:52 AM #111 Banned Camp   Joined: Mar 2017 From: . Posts: 338 Thanks: 8 Math Focus: Number theory We are now no longer close to cracking it. It is already solved. Coming up in a few hours. Also it indeed is beautiful and simpler than all those trials we've tackled. This has been possible through trusting instincts.
 July 13th, 2017, 08:42 PM #112 Banned Camp   Joined: Mar 2017 From: . Posts: 338 Thanks: 8 Math Focus: Number theory Proof of Fermat's last theorem. lemma If $a=b$, then $a^n+b^n\neq c^n$ for positive integers $a$, $b$, $c$ and $n>2$. proof If $a=b$, \begin{align*} a^n+a^n&=c^n\\ 2a^n&=c^n\\ 2&=\frac{c^n}{a^n}\\ 2&=(\frac{c}{a})^n \end{align*} If $\frac{c}{a}$ is a fraction then $(\frac{c}{a})^n$ will be a fraction since $(\frac{c}{a})^n=\prod \limits^n\frac{c}{a}$, implying $c^n$ would not divide $a^n$. Thus, $2=(\frac{c}{a})^n$ will hold iff $\frac{c}{a}$ is an integer. The only value of $\frac{c}{a}$ that satisfies the equation such that $n$ is a positive integer is $\frac{c}{a}=2$ so that $n=1$. Thus, $a^n+b^n\neq c^n$ for positive integers $a$, $b$ $c$ and $n$ such that $n>2$ and $a=b$. We therefore assume $a\neq b$. We multiply both sides of the equation $c^n=a^n+b^n$ by $a^n-b^n$ \begin{align*} c^n(a^n-b^n)&=(a^n+b^n)(a^n-b^n)\\ c^n(a^n-b^n)&=(a^n)^2-(b^n)^2\\ c^n(a^n-b^n)&=(a^2)^n-(b^2)^n\tag{1} \end{align*} When factoring, \begin{align*} a^n-b^n&=(a-b)(a^{n-1}+a^{n-2}b+a^{n-3}b^2+\cdots +ab^{n-2}+b^{n-1})\\ a^n-b^n&=(a-b)\sum\limits_{i=1}^na^{n-i}b^{i-1} \end{align*} Therefore \begin{align*} (a^2)^n-(b^2)^n&=(a^2-b^2)\{(a^2)^{n-1}+(a^2)^{n-2}b^2+\cdots +a^2(b^2)^{n-2}+(b^2)^{n-1}\}\\ (a^2)^n-(b^2)^n&=(a^2-b^2)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1} \end{align*} We substitute this in 1. $$c^n(a-b)\sum\limits_{i=1}^na^{n-i}b^{i-1}=(a^2-b^2)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}$$ We divide both sides of the equation by $(a-b)$ \begin{align*} c^n\sum\limits_{i=1}^na^{n-i}b^{i-1}&=\frac{(a+b)(a-b)}{(a-b)}\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}\\ c^n\sum\limits_{i=1}^na^{n-i}b^{i-1}&=(a+b)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1} \end{align*} \begin{align*} c^n&=\frac{(a+b)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}}{\sum\limits_{i=1}^na^{n-i}b^{i-1}}\\ a^n+b^n&=\frac{(a+b)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}}{\sum\limits_{i=1}^na^{n-i}b^{i-1}} \end{align*} theorem $a^n+b^n\neq c^n$ for positive integers $a$, $b$, $c$ and $n>2$. proof Let $\frac{\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}}{\sum\limits_{i=1}^na^{n-i}b^{i-1}}$ be $\frac{x}{y}$. $$a^n+b^n=\frac{(a+b)}{y}x=a\frac{x}{y}+b\frac{x}{ y}$$ The equation above holds iff either $a+b=y$ so that $a^n+b^n=x$ or $\frac{x}{y}=1$ so that $a^n+b^n=a+b$.\\ If $\frac{x}{y}=1$ then $x=y$. Therefore, $$\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}=\sum\limits_{i=1}^na^{n-i}b^{i-1}$$ $a^n+b^n=a+b$ if $n=1$. Therefore $x=y$ should hold for $n=1$. We substitute $n=1$ \begin{align*} \sum\limits_{i=1}^1(a^2)^{n-i}(b^2)^{i-1}&=\sum\limits_{i=1}^1a^{n-i}b^{i-1}\\ (a^2)^0(b^2)^0&=a^0b^0\\ 1&=1 \end{align*} If $a+b=y$, $$a+b=\sum\limits_{i=1}^na^{n-i}b^{i-1}$$ This equation is satisfied if $n=2$ such that \begin{align*} a+b&=a^1b^0+a^0b^1\\ a+b&=a+b \end{align*} Therefore $a^n+b^n=x$ should hold for $n=2$ \begin{align*} a^n+b^n&=\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}\\ a^2+b^2&=\sum\limits_{i=1}^2(a^2)^{n-i}(b^2)^{i-1}\\ a^2+b^2&=(a^2)^1(b^2)^0+(b^2)^1(a^2)^0\\ a^2+b^2&=a^2+b^2 \end{align*} Therefore the equation $$a^n+b^n =\frac{(a+b)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}}{\sum\limits_{i=1}^na^{n-i}b^{i-1}}$$ holds for $n=1$ and $n=2$ only. Meaning $a^n+b^n=c^n$, such that $a$, $b$ and $c$ are positive integers holds for $n=1$ and $n=2$ only. Therefore $a^n+b^n\neq c^n$ for positive integers $a$, $b$ and $c$ and $n>2$.
July 13th, 2017, 09:15 PM   #113
Senior Member

Joined: May 2016
From: USA

Posts: 993
Thanks: 407

Quote:
 Originally Posted by Mariga Proof of Fermat's last theorem. lemma If $a=b$, then $a^n+b^n\neq c^n$ for positive integers $a$, $b$, $c$ and $n>2$. proof If $a=b$, \begin{align*} a^n+a^n&=c^n\\ 2a^n&=c^n\\ 2&=\frac{c^n}{a^n}\\ 2&=(\frac{c}{a})^n \end{align*} If $\frac{c}{a}$ is a fraction then $(\frac{c}{a})^n$ will be a fraction since $(\frac{c}{a})^n=\prod \limits^n\frac{c}{a}$, implying $c^n$ would not divide $a^n$. Thus, $2=(\frac{c}{a})^n$ will hold iff $\frac{c}{a}$ is an integer. The only value of $\frac{c}{a}$ that satisfies the equation such that $n$ is a positive integer is $\frac{c}{a}=2$ so that $n=1$. Thus, $a^n+b^n\neq c^n$ for positive integers $a$, $b$ $c$ and $n$ such that $n>2$ and $a=b$. We therefore assume $a\neq b$. We multiply both sides of the equation $c^n=a^n+b^n$ by $a^n-b^n$ \begin{align*} c^n(a^n-b^n)&=(a^n+b^n)(a^n-b^n)\\ c^n(a^n-b^n)&=(a^n)^2-(b^n)^2\\ c^n(a^n-b^n)&=(a^2)^n-(b^2)^n\tag{1} \end{align*} When factoring, \begin{align*} a^n-b^n&=(a-b)(a^{n-1}+a^{n-2}b+a^{n-3}b^2+\cdots +ab^{n-2}+b^{n-1})\\ a^n-b^n&=(a-b)\sum\limits_{i=1}^na^{n-i}b^{i-1} \end{align*} Therefore \begin{align*} (a^2)^n-(b^2)^n&=(a^2-b^2)\{(a^2)^{n-1}+(a^2)^{n-2}b^2+\cdots +a^2(b^2)^{n-2}+(b^2)^{n-1}\}\\ (a^2)^n-(b^2)^n&=(a^2-b^2)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1} \end{align*} We substitute this in 1. $$c^n(a-b)\sum\limits_{i=1}^na^{n-i}b^{i-1}=(a^2-b^2)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}$$ We divide both sides of the equation by $(a-b)$ \begin{align*} c^n\sum\limits_{i=1}^na^{n-i}b^{i-1}&=\frac{(a+b)(a-b)}{(a-b)}\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}\\ c^n\sum\limits_{i=1}^na^{n-i}b^{i-1}&=(a+b)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1} \end{align*} \begin{align*} c^n&=\frac{(a+b)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}}{\sum\limits_{i=1}^na^{n-i}b^{i-1}}\\ a^n+b^n&=\frac{(a+b)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}}{\sum\limits_{i=1}^na^{n-i}b^{i-1}} \end{align*} theorem $a^n+b^n\neq c^n$ for positive integers $a$, $b$, $c$ and $n>2$. proof Let $\frac{\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}}{\sum\limits_{i=1}^na^{n-i}b^{i-1}}$ be $\frac{x}{y}$. $$a^n+b^n=\frac{(a+b)}{y}x=a\frac{x}{y}+b\frac{x}{ y}$$ The equation above holds iff either $a+b=y$ so that $a^n+b^n=x$ or $\frac{x}{y}=1$ so that $a^n+b^n=a+b$.\\ If $\frac{x}{y}=1$ then $x=y$. Therefore, $$\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}=\sum\limits_{i=1}^na^{n-i}b^{i-1}$$ $a^n+b^n=a+b$ if $n=1$. Therefore $x=y$ should hold for $n=1$. We substitute $n=1$ \begin{align*} \sum\limits_{i=1}^1(a^2)^{n-i}(b^2)^{i-1}&=\sum\limits_{i=1}^1a^{n-i}b^{i-1}\\ (a^2)^0(b^2)^0&=a^0b^0\\ 1&=1 \end{align*} If $a+b=y$, $$a+b=\sum\limits_{i=1}^na^{n-i}b^{i-1}$$ This equation is satisfied if $n=2$ such that \begin{align*} a+b&=a^1b^0+a^0b^1\\ a+b&=a+b \end{align*} Therefore $a^n+b^n=x$ should hold for $n=2$ \begin{align*} a^n+b^n&=\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}\\ a^2+b^2&=\sum\limits_{i=1}^2(a^2)^{n-i}(b^2)^{i-1}\\ a^2+b^2&=(a^2)^1(b^2)^0+(b^2)^1(a^2)^0\\ a^2+b^2&=a^2+b^2 \end{align*} Therefore the equation $$a^n+b^n =\frac{(a+b)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}}{\sum\limits_{i=1}^na^{n-i}b^{i-1}}$$ holds for $n=1$ and $n=2$ only. Meaning $a^n+b^n=c^n$, such that $a$, $b$ and $c$ are positive integers holds for $n=1$ and $n=2$ only. Therefore $a^n+b^n\neq c^n$ for positive integers $a$, $b$ and $c$ and $n>2$.
It is very late at night here; I am sleepy and cannot look at this in detail. But you show that a certain proposition may be valid if n = 1 or if n = 2, and then assert, without any proof that I see in my drowsy state, that the same proposition cannot be valid if n > 2. Don't you need to prove that?

July 13th, 2017, 09:39 PM   #114
Senior Member

Joined: May 2013

Posts: 115
Thanks: 10

Quote:
 Originally Posted by Mariga The equation above holds iff either $a+b=y$ so that $a^n+b^n=x$ or $\frac{x}{y}=1$ so that $a^n+b^n=a+b$.\\
Prove it

July 14th, 2017, 10:04 AM   #115
Banned Camp

Joined: Mar 2017
From: .

Posts: 338
Thanks: 8

Math Focus: Number theory
Quote:
 Originally Posted by JeffM1 It is very late at night here; I am sleepy and cannot look at this in detail. But you show that a certain proposition may be valid if n = 1 or if n = 2, and then assert, without any proof that I see in my drowsy state, that the same proposition cannot be valid if n > 2. Don't you need to prove that?
Go through it again. I've shown that $a^n+b^=c^n$ for positive integers $a$, $b$, $c$ and $n$ holds iff $n=1$ or $n=2$.

Isn't that a sufficient proof?

July 14th, 2017, 10:10 AM   #116
Senior Member

Joined: May 2016
From: USA

Posts: 993
Thanks: 407

I may address this in a number of posts because I have other demands on my time.

Quote:
 Originally Posted by Mariga Proof of Fermat's last theorem. lemma If $a=b$, then $a^n+b^n\neq c^n$ for positive integers $a$, $b$, $c$ and $n>2$. proof If $a=b$, \begin{align*} a^n+a^n&=c^n\\ 2a^n&=c^n\\ 2&=\frac{c^n}{a^n}\\ 2&=(\frac{c}{a})^n \end{align*} If $\frac{c}{a}$ is a fraction then $(\frac{c}{a})^n$ will be a fraction since $(\frac{c}{a})^n=\prod \limits^n\frac{c}{a}$, implying $c^n$ would not divide $a^n$. Thus, $2=(\frac{c}{a})^n$ will hold iff $\frac{c}{a}$ is an integer. The only value of $\frac{c}{a}$ that satisfies the equation such that $n$ is a positive integer is $\frac{c}{a}=2$ so that $n=1$. Thus, $a^n+b^n\neq c^n$ for positive integers $a$, $b$ $c$ and $n$ such that $n>2$ and $a=b$.
I do not believe that is a valid proof, but I am pretty sure that a valid proof could be constructed using the Fundamental Theorem of Arithmetic so I am not going to fuss about it.

Quote:
 Originally Posted by Mariga We therefore assume $a\neq b$.... [to get] \begin{align*} c^n\sum\limits_{i=1}^na^{n-i}b^{i-1}&=\frac{(a+b)(a-b)}{(a-b)}\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}\\ c^n\sum\limits_{i=1}^na^{n-i}b^{i-1}&=(a+b)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1} \end{align*} \begin{align*} c^n&=\frac{(a+b)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}}{\sum\limits_{i=1}^na^{n-i}b^{i-1}}\\ a^n+b^n&=\frac{(a+b)\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}}{\sum\limits_{i=1}^na^{n-i}b^{i-1}} \end{align*}
This looks like algebra that has been checked before several times (in fact I may have got this exact format in a previous post) so I am going to accept it provisionally.

Quote:
 Originally Posted by Mariga Let $\frac{\sum\limits_{i=1}^n(a^2)^{n-i}(b^2)^{i-1}}{\sum\limits_{i=1}^na^{n-i}b^{i-1}}$ be $\frac{x}{y}$. $$a^n+b^n=\frac{(a+b)}{y}x=a\frac{x}{y}+b\frac{x}{ y}$$ The equation above holds iff either $a+b=y$ so that $a^n+b^n=x$ or $\frac{x}{y}=1$ so that $a^n+b^n=a+b$.
As bruno cogently pointed out, this is merely asserted rather than proved.

Consider the case when n = 1.

$\dfrac{x}{y} = \dfrac{\sum\limits_{j=1}^n(a^2)^{(n-j)}(b^2)^{(j-1)}}{\sum\limits_{i=1}^na^{(n-j)}b^{(j-1)}} \iff$

$\dfrac{x}{y} = \dfrac{(a^2)^{(1-1)}(b^2)^{(1- 1)}}{a^{(1-1)}b^{(1- 1)}} \iff$

$\dfrac{x}{y} = 1 \iff$

$\dfrac{x}{y} * (a + b) = a^1 + b^1.$ Good so far.

How about when n = 2.

$\dfrac{x}{y} = \dfrac{\sum\limits_{j=1}^n(a^2)^{(n-j)}(b^2)^{(j-1)}}{\sum\limits_{i=1}^na^{(n-j)}b^{(j-1)}} \iff$

$\dfrac{x}{y} = \dfrac{(a^2)^{(2-1)}(b^2)^{(1- 1)} + (a^2)^{(2-2)}(b^2)^{(2-1)}}{a^{(2-1)}b^{(1- 1)} + a^{(2-2)}b^{(2-1)}} \iff$

$\dfrac{x}{y} = \dfrac{a^2 + b^2}{a + b} \iff$

$\dfrac{x}{y} * (a + b) = a^2 + b^2.$

Thus, it is true that

$\{n = 1 \text { or } n = 2\} \iff \left \{\dfrac{x}{y} = 1 \text { or } y = a + b \right \}.$

But that says nothing whatsoever if n > 2. Thus the rest of the proof hangs in the air.

 July 15th, 2017, 12:03 AM #117 Banned Camp   Joined: Mar 2017 From: . Posts: 338 Thanks: 8 Math Focus: Number theory I see your point guys. More work needs to be done on this. I'll see what I'll make of it.
 July 15th, 2017, 04:28 AM #118 Math Team   Joined: Oct 2011 From: Ottawa Ontario, Canada Posts: 12,095 Thanks: 795 ...and Big Pete Fermat smiles from above...
 July 17th, 2017, 05:09 AM #119 Banned Camp   Joined: Dec 2012 Posts: 1,028 Thanks: 24 Once again: find a specific property of the powers of integers, the difference from n=2 and n>2, and a new tools to play with them... or be sure you cannot say "eureka"... I believe my Complicate Modulus Algebra is the only chance after Wiles... and I'm still working on...
 July 19th, 2017, 03:05 AM #120 Banned Camp   Joined: Mar 2017 From: . Posts: 338 Thanks: 8 Math Focus: Number theory Denis, I wouldn't want you to have a heart attack. Brace yourself. The next proof is the real one. Complicatemodulus you are indeed right. I need to include more tools because I've been just revolving around one concept for quite some time and it isn't sufficient enough on its own. The proof I am soon going to give might show $a^n+b^n=c^n$ holds iff $n=1$ or $n=2$ and thus I wouldn't need to prove for $n>2$. It will lock on those two. That's the beauty of an algebraic proof.

 Tags fermat, proof, simplest, theorem

### fermat last theorem simple proof 2017

Click on a term to search for related topics.
 Thread Tools Display Modes Linear Mode

 Similar Threads Thread Thread Starter Forum Replies Last Post RanberSingh Number Theory 2 April 27th, 2017 08:06 AM MrAwojobi Number Theory 1 September 29th, 2015 07:22 AM M_B_S Number Theory 15 July 29th, 2015 05:14 AM RanberSingh New Users 3 August 10th, 2014 01:44 PM MrAwojobi Number Theory 21 January 8th, 2011 09:11 AM

 Contact - Home - Forums - Cryptocurrency Forum - Top